Effect of ASP2205 fumarate, a novel 5-HT2C receptor agonist, on urethral closure function in rats - Takao Ishigami; Koji Ueshima; Masashi Ukai; Norio Asai; Hajime Takamatsu; Masanori Yokono; Masahiro Takeda; Noriyuki Masuda (Elsevier, 2019)
The pharmacological profile of ASP2205 fumarate (ASP2205), a novel 5-HT2C receptor agonist, was evaluated in vitro and in vivo. ASP2205 showed potent and selective agonistic activity for the human 5-HT2C receptor, with an EC50 of 0.85 nM in the intracellular Ca2+ mobilization assay. Rat 5-HT2C receptor was also activated by ASP2205 with an EC50 of 2.5 nM. Intraduodenal administration (i.d.) of ASP2205 (0.1-1 mg/kg) significantly elevated the leak point pressure (LPP) in anesthetized rats in a dose-dependent manner. This ASP2205 (0.3 mg/kg i.d.)-induced LPP elevation was inhibited by SB242084 (0.3 mg/kg i.v.), a selective 5-HT2C receptor antagonist. Urethral closure responses induced by intravesical pressure loading in rats were enhanced by ASP2205 (0.3 mg/kg i.v.), which was abolished by pretreatment with SB242084 (0.3 mg/kg i.v.) and bilateral transection of the pudendal nerve. In contrast, ASP2205 (0.3 mg/kg i.v.) did not change the resting urethral pressure in rats. These results indicate that ASP2205 can enhance the pudendal nerve-mediated urethral closure reflex via the 5-HT2C receptor, resulting in the prevention of involuntary urine loss. Keywords: ASP2205, 5-HT2C receptor, Leak point pressure, Urethral closure response, Urethral pressure